Citrus fruits and their flavonoids in inflammatory bowel disease: an overview. Issue 1 (2nd January 2020) - Musumeci, Laura; Maugeri, Alessandro; Cirmi, Santa; Lombardo, Giovanni Enrico; Russo, Caterina; Gangemi, Sebastiano; Calapai, Gioacchino; Navarra, Michele
Abstract: Inflammatory bowel disease (IBD), with its major manifestations being Crohn's disease and ulcerative colitis, belongs to the gastrointestinal inflammatory disorders, whose main therapeutic approach is represented by synthetic anti-inflammatory drugs. However, they are often accompanied by many side effects that shifted the interest of the scientific community towards natural products. In this context, several studies asserted the anti-IBD effects of Citrus fruits and their flavonoids, thus the aim of the present review is to provide robust evidence favouring their role in the prevention and treatment of IBD. Key mechanisms relate to their anti-inflammatory and antioxidant properties, as well as their ability to modulate gut microbiota. All the findings collected in this review, lay the foundations for further studies in human with the aim of evaluating the concrete applicability as a novel preventive and therapeutic approach of Citrus fruits and their flavonoids.